Falling Corporate Tax Rates in the EU: Is there a case for harmonisation? - María T. Álvarez-Martínez; Salvador Barrios; Diego d'Andría; Maria Gesualdo; Jonathan Pycroft; Dimitrios Pontikakis (European Commission, Joint Research Centre (JRC), 2016)
In a globalised world economy where capital is highly mobile governments are eager to attract foreign investors by lowering their corporate tax rates. EU countries have been particularly active in this respect given that capital can move freely across EU member states' borders thanks to reforms removing major obstacles to cross-border investments. Multinationals are therefore in a good position to exploit the tax loopholes associated with the complexity and multiplicity of tax regimes in the EU. As a result tax revenues and tax levels might be distorted and a closer coordination of tax rate setting might be warranted. In this paper we quantify the macroeconomic consequences of changing corporate tax rates depending on a given EU country specific situation, in particular in terms of economic size and tax level and structure, and we investigate the possible case for a closer coordination of corporate tax policies in the EU. We use a computable general equilibrium (CGE) model reflecting countries' heterogeneity to assess the economic impact of corporate tax changes and the possible economic impacts of uncoordinated and coordinated tax policy reforms in the EU. The aim of this paper is to contribute to the ongoing debate about the desirability, modality and likely impact of alternative policy solutions to the challenges posed by tax competition and aggressive tax planning. We find that corporate income tax rates can generate substantial responses within the implementing country as well as beyond its own borders depending on the country size. Harmonisation of CIT rates would involve winners and losers and it may have costs for the EU and as such, may be best pursued gradually and as part of a broader package of corporate tax reform on tax bases and government transfers.
Keywords: 330; corporate taxation; computable general equilibrium models; tax harmonization